The Relationship Between Internal Quality Assurance, Internal Quality Audit, and Accreditation Outcomes: An Exploratory Case Study at A Private Higher Education Institution - Hartono, Edy; Hartono, Wahyu; Prasasti Suminar, Ratna; Hidayat, Firman (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Internal quality assurance (IQA) serves as a fundamental pillar in the sustainable governance of higher education. However, empirical studies examining the relationship between IQA, internal quality audits, and accreditation outcomes remain limited particularly within the context of private higher education institutions. This study aims to explore the potential correlations between the performance of internal quality assurance as measured through monitoring and evaluation (M&E) activities the results of Internal Quality Audits (AMI), and program-level accreditation outcomes. Employing a descriptive-correlational quantitative approach, the study analyzes 2024 M&E data, AMI scores, and accreditation results from 2025 and prior periods, focusing on four academic programs within a single private university. Internal quality assurance is assessed using four key indicators: consistency in monitoring and evaluation, achievement of quality standards, completeness of documentation, and follow-up on evaluation results. The analysis reveals a tendency toward positive correlations among IQA scores, audit scores, and changes in accreditation outcomes. These findings suggest that internal quality assurance and internal audits may function as supportive mechanisms for achieving accreditation goals, though the results remain contextual and exploratory in nature.